THE INFLUENCE OF PERSONALITY, PEDAGOGICAL COMPETENCE, AND ACHIEVEMENT MOTIVATION ON EARLY CHILDHOOD TEACHER PERFORMANCE IN ACEH TAMIANG REGENCY - Wan War Safitria; Hera Yanti; Alfi Syahrin (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
This study aims to: (1) analyze the effect of personality on the achievement motivation of early childhood education teachers in Aceh Tamiang Regency; (2) analyze the effect of pedagogical competence on the achievement motivation of PAUD teachers in Aceh Tamiang Regency; (3) analyze the effect of personality on the performance of PAUD teachers in Aceh Tamiang Regency; (4) analyze the effect of pedagogical competence on the performance of PAUD teachers in Aceh Tamiang Regency; (5) analyze the effect of achievement motivation on the performance of PAUD teachers in Aceh Tamiang Regency; and (6) analyze the simultaneous effect of personality, pedagogical competence, and achievement motivation on the performance of PAUD teachers in Aceh Tamiang Regency. This research uses a quantitative approach with an associative research design. The population consisted of 784 PAUD teachers, with a sample of 100 selected proportionally using Slovin’s formula and probability sampling techniques. The results indicate that: (1) there is a positive and significant effect between personality and teachers’ achievement motivation, (2) pedagogical competence and teachers’ achievement motivation, (3) personality and teacher performance, (4) pedagogical competence and teacher performance, (5) achievement motivation and teacher performance. All relationships are statistically significant with a significance level below 0.05. (6) Simultaneously, personality, pedagogical competence, and achievement motivation contribute significantly to teacher performance, with a coefficient of determination (R²) of 0.934 or 93.4%.Based on the findings, it is recommended that schools and educational policymakers give serious attention to developing teachers’ personality and pedagogical competence as the main foundation for improving performance. Efforts in character building, instilling values of responsibility, discipline, and work ethic should be conducted continuously through internal development and constructive supervision.